Bilioenteric Fistula - Not any more a contraindication for Laparoscopic Cholecystectomy - Mondal, Samiron Kumar; Roy, Sharmistha (Bangladesh Critical Care Journal, 2015)
Background: Bilioenteric fistulas include cholecystoduodenal fistula, cholecystocolic fistula, and cholecystogastric fistula. They are known but rare complication of cholecystitis. Previously presence of any cholecystoenteric fistula was an indication to convert laparoscopic cholecystectomy to open operation1. But with time and experience new techniques, new technology and expertise has developed in the laparoscopic field and now the scenario is changed. This is our experience in a tertiary care diabetic hospital where we encountered 21 cases of cholecystoenteric fistula during laparoscopic cholecystectomy over a period of 2 years. Our series: From January 2013 to January 2015 we performed 1191 cases of laparoscopic cholecystectomy in our unit. We encountered 12 cases of cholecystoduodenal fistula, 7 cases of cholecystocolic fistula and 2 cases of cholecystogastric fistula. All cases were diagnosed during laparoscopy, and were dealt with laparoscopy. Intracorporeal suturing was used in all cases. Observation: Successful per operative diagnosis requires suspicion and careful adhesiolysis in all cases. Avoiding conversion to open operation reduces hospital stay, pain, wound infection and chest complications associated with upper abdominal incision. As the fistulous tract is usually near the fundus and far away from Callots there is not much increased risk of common bile duct injury. Conclusion: Cholecystoenteric fistulas can now safely be managed laparoscopically in advanced centers by experienced surgeon. Bangladesh Crit Care J March 2015; 3 (1): 7-8